Calligraphy Ornaments as Islamic Identity in the Bubungan Tinggi and the Gajah Baliku House, Teluk Selong, South Borneo, Indonesia - Heldiansyah, J.C.; Aufa, Naimatul; Wastuty, Prima Widia; Saud, Mohammad Ibnu (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
Islamic values are applied in architecture by avoiding motifs of living creatures, yet use floral motifs and Arabic calligraphy instead. Each ornament has a specific shape and meaning. While floral ornaments in traditional Banjar architecture are well-researched, studies on Arabic calligraphy are limited due to their complexity. This research aims to reveal the forms and meanings of Arabic calligraphy in traditional Banjar architecture, especially in the Bubungan Tinggi and Gajah Baliku houses. This understanding can help preserve and pass on the art of Arabic calligraphy and its values to future generations. The research employs an interpretive qualitative analysis method. Each letter, word, sentence, and geometric pattern that makes up calligraphy is identified to understand the form of calligraphy. Visual reconstruction was performed by simplifying the calligraphy to obtain certain sentences to match with their equivalents in the Quran and Hadith. The research found that the forms of Arabic calligraphy used included Quranic verses, monotheistic statements, prayers, names of the Prophet's companions, and protective prayers. The meanings conveyed statements of Allah's oneness, belief in Prophet Muhammad, and requests for protection from Allah. All Arabic calligraphy is placed on the tawing halat, indicating the homeowner's identity and social status, thus showcasing the Islamic identity of the architecture.